Porous Titanium Granules and Blood for Bone Regeneration around Dental Implants: Report of Four Cases and Review of the Literature - Andreas Thor (Case Reports in Dentistry)
A regenerative procedure treating a local osseous defect around titanium dental implant using porous titanium granules is described in four patients. Porous titanium granules represent, for maxillofacial surgery, a new alternative in augmenting osseous defects. Its earliest application was in the field of orthopedics for stabilization of tibia plateau fractures and for reoperations in prosthetic fixation of femoral stems. There is emerging scientific evidence regarding titanium for its potential use in the maxillofacial area and porous titanium granules are now commercially available. The scientific background for the osteoconductive use of porous titanium granules is elucidated in this paper and the supporting literature is reviewed.